Clinical significance of costimulatory molecules CD40/CD40L and CD134/CD134L in coronary heart disease: A case-control study. Issue 32 (August 2017) - Chen, Jun; Li, Jian-Hao; Zhao, Shan-Jun; Wang, Da-Yu; Zhang, Wen-Zhu; Liang, Wei-Jie
Abstract : Abstract: The aim of the study was to evaluate the potential role of CD40/CD40 ligand (CD40L) and CD134/CD134 ligand (CD134L) in the development of coronary heart disease (CHD) via the performance of a case-control study. The research objects were 234 cases of CHD patients and 120 cases of well-matched normal controls. Following the separation of peripheral blood mononuclear cells (PBMCs), real-time quantitative PCR (qRT-PCR), Western blot, immunohistochemistry, and flow cytometry were applied for the detection of mRNA levels and expression levels of CD40/CD40L and CD134/CD134L; meanwhile, intercellular adhesion molecule-1 (ICAM-1) and Fas protein mRNA levels were detected using qRT-PCR. There was no statistical difference in the comparison of baseline characteristics between groups, indicating comparability between groups. qRT-PCR and Western blot analysis indicated that CD40/CD40L and CD134/CD134L mRNA and protein expression levels were all increased in the CHD group than those in the control group. Flow cytometry further confirmed the similar tendency. Meanwhile, ICAM-1 and Fas protein mRNA levels were elevated in the CHD group and positively correlated with the above parameters. Furthermore, CD40/CD40L expression rates were negatively correlated with gender and different types of CHD. Meanwhile, CD134/CD134L expressions were also higher in male patients, in patients with family history, previous history of hypertension, diabetes, and cerebrovascular diseases. CD40/CD40L and CD134/CD134L are increased and may have potential correlation with clinical pathological features of patients with CHD. Further in-depth exploration of costimulatory molecules for CHD guidance as well as intrinsic mechanisms are needed combined with in vivo and in vitro experiments.